2017
DOI: 10.5194/amt-10-1043-2017
|View full text |Cite
|
Sign up to set email alerts
|

The filter-loading effect by ambient aerosols in filter absorption photometers depends on the coating of the sampled particles

Abstract: Abstract. Black carbon is a primary aerosol tracer for high-temperature combustion emissions and can be used to characterize the time evolution of its sources. It is correlated with a decrease in public health and contributes to atmospheric warming. Black carbon measurements are usually conducted with absorption filter photometers, which are prone to several artifacts, including the filter-loading effect – a saturation of the instrumental response due to the accumulation of the sample in the filter matrix. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 70 publications
3
61
0
Order By: Relevance
“…Therefore, it is often challenging to distinguish between light absorption by BC and by BrC, especially if the BC concentrations are high (e.g., for flaming combustion). Second, most online instruments use 1-7 fixed wavelengths for light absorption measurements (Drinovec et al, 2015(Drinovec et al, , 2017Lewis et al, 2008;Virkkula et al, 2005), which may not be sufficient to fully characterize spectral absorption properties of BB BrC emissions . In contrast to online instruments, the approach used in this study -measurements of BrC light absorption in extracts -eliminates the interference of BC absorption and allows recording high-resolution (i.e., ∼ 1 nm) absorption spectra over a large wavelength range (i.e., 190-900 nm, for this work).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is often challenging to distinguish between light absorption by BC and by BrC, especially if the BC concentrations are high (e.g., for flaming combustion). Second, most online instruments use 1-7 fixed wavelengths for light absorption measurements (Drinovec et al, 2015(Drinovec et al, , 2017Lewis et al, 2008;Virkkula et al, 2005), which may not be sufficient to fully characterize spectral absorption properties of BB BrC emissions . In contrast to online instruments, the approach used in this study -measurements of BrC light absorption in extracts -eliminates the interference of BC absorption and allows recording high-resolution (i.e., ∼ 1 nm) absorption spectra over a large wavelength range (i.e., 190-900 nm, for this work).…”
Section: Resultsmentioning
confidence: 99%
“…15 Therefore, it is often challenging to distinguish between light absorption by BC and by BrC, especially if the BC concentrations are high (e.g., for flaming combustion). Second, most online instruments use 1-7 fixed wavelengths for light absorption measurements (Drinovec et al, 2015(Drinovec et al, , 2017Lewis et al, 2008;Virkkula et al, 2005), which may not be sufficient to fully characterize spectral absorption properties of BB BrC emissions . 20…”
Section: Resultsmentioning
confidence: 99%
“…Light-absorbing organic aerosols are also known as brown carbon (BrC) since they absorb blue light significantly but have practically zero absorption in the red band, yielding brownish colours . The distinction between the light absorption by BC and BrC in field and laboratory studies has relied on the explicit assumption that no carbonaceous particle type except BC absorbs solar radiation at a wavelength of ∼ 700 nm or larger (Bahadur et al, 2012;Kirchstetter and Thatcher, 2012;Lu et al, 2015;Drinovec et al, 2017). This common assumption has been used in spite of the finding by Alexander et al (2008), who showed a sizable absorption by a specific class of BrC at longer wavelengths.…”
Section: Introductionmentioning
confidence: 85%